The semiotics and politics of the female body: A comprehensive analysis of Elfen Lied and its opening song (Gilgameš, 2019)
This paper develops an exhaustive analysis of the Japanese animation series Elfen Lied (2004) and its opening song, “Lilium”, which is an exceptional case within its field of production because its lyrics are written in Latin. The purpose of my analysis is to determine if “Lilium” and its visual presentation really have something to do (thematically and stylistically) with the series it presents, or not. My hypothesis is that "Lilium", both in its musical level and in its visual presentation, fulfils all the formal characteristics of both a lied and an overture; and, given the latter, anticipates core thematic and stylistic elements of the work it precedes. Moreover, it even subtly anticipates the ideological content of the series, which consists of a critical reading of gender roles and feminism in contemporary Japanese and global society. To demonstrate these hypotheses, I made a detailed analysis of Elfen Lied, paying special attention to its animated adaptation but not ignoring its original manga version; and then I analyzed "Lilium" in its three aspects: its visual presentation, its lyric and its musical score. I have analyzed and emphasized how the abundant intertextualities present in "Lilium" were productive for creating music and for transmitting the artistic and ideological content present in the series. The paper adopts an interdisciplinary perspective, and uses theoretical tools from the fields of semiotics, intertextuality, and reception theory.